Effective prevention of burnout in elite athletes and high-level coaches - Lemyre, P. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
It has been argued that only individuals originally fueled by a passion or a sacred fire for their involvement and dedication to an activity, may experience the debilitating consequences of burning out (Pines, 1993). Representing more than a simple reaction to an accumulation of stress, burnout in athletes and coaches is a multidimensional syndrome that is typically manifested by a feeling of dysphoria affecting the welfare of the individuals, leading to a reduction in the levels vitality and the quality of motivation, as well as as affecting of the individuals` efforts towards a desired goal. Based on a series of subsequent studies on elite athletes and high-level coaches, this presentation will make the argument that the early identification of at-risk profiles represents an effective measure to prevent burnout in elite athletes and high-level coaches. Athletes and coaches motivated by unrealistic or unstable goals are more predisposed to develop symptoms of burnout and engage in a downward spiral leading individuals from exhaustion to disengagement from sports. While most athletes and coaches will typically describe their initial commitment to sports as being highly intrinsically motivated, these reasons for being involved in sports may change during a season or a career. When their motivation becomes purely extrinsic or that they lose the motivation to be involved in sports, as they persist in their sport-related role they will become increasingly at-risk of burning out (Lemyre, Hall, & Roberts , 2008; Bentzen, Lemyre, & Kenttä, 2015). Their actions are no longer self-determined, an imbalance develops between the perception of effort and the perceived return on personal investment in sports. Current study findings clearly suggest that assessing one`s motives for competing or coaching in sports, one`s perceived achievement climate and felt level of need support, as well as one`s perceived level of competence and expression of perfectionist tendencies, allows for a reliable identification of at-risk profiles burnout. Subsequent systematic monitoring of changes in quality of motivation and perceived need support in individuals with at-risk profiles serves an effective prevention tool to justly intervene prior to coaches and athletes burning out.